Pengaruh Ukuran Perusahaan, Umur Perusahaan, Profitabilitas, Leverage dan Pertumbuhan Perusahaan terhadap Pengungkapan Corporate Social Responsibility - Ni Kadek Elis Pitriani; Ni Luh Gde Novitasari; Ni Luh Putu Widhiastuti (Universitas Negeri Padang, 2024)
Disclosure of corporate social responsibility (CSR) is a communication process regarding the social and environmental impacts of the economic activities of an organization or company on special interested groups and on society as a whole. This study aims to examine the effect of firm size, company age, profitability, leverage and company growth on corporate social responsibility disclosure. The population in this study were all banking companies listed on the Indonesia Stock Exchange in 2020- 2022 as many as 47 companies. The sample used is as many as 41 companies based on purposive sampling method, namely the sampling technique with certain criteria, so the total of companies for the 3 periods was 123 sample. The data used in this study is secondary data. The analytical technique used multiple linear regression analysis test. The results show that firm size, leverage and company growth has a positive effect on corporate social responsibility disclosure, while company age and profitability have no effect on corporate social responsibility disclosure.